Treasured memories : tales of buried belongings in wartime Estonia - Burström, Mats (Nordic Academic Press, 2012)
In the autumn of 1944, around 70,000 people fled Estonia in the face of the Red Army's advance; most of them believed the Soviet occupation would be short-lived and they would soon be able to return home. A comprehensive study of a common yet neglected phenomenon, this book tells the stories of the hoards of valuable belongings hidden by these Estonian escapees. The sheer variety of objectsincluding those that remain buried, those that vanished, and those that were recoveredtouches upon all levels of history, from personal memories to high politics. In essence, this work of contemporary archaeology not only reflects upon the intimate relationship between material culture and memory, but also demonstrates how events on the world stage can shape the fate of individual families across generations.